Understanding tourists' attitudes toward interventions for the Great Barrier Reef: an extension of the norm activation model. Issue 6 (3rd June 2022) - Ritchie, Brent W.; Prideaux, Bruce; Thompson, Michelle; Demeter, Csilla
Abstract: Coral reefs provide important ecosystem services as well as economic and cultural benefits to society. Yet they are under significant threat from anthropogenic and natural threats, including climate change. Australia's Great Barrier Reef (GBR) is one such reef undergoing significant change. More radical interventions that go beyond traditional forms of management are being considered to help repair and restore the GBR. These are based on science and technologies that have yet to be widely tested. This paper reports on a study that seeks to identify and understand support for such interventions, and to understand the antecedents that explain support. The Norm Activation Model (NAM) was extended with a sample of 468 domestic and international tourists to Cairns, Australia. Personal norms had the largest direct influence on support for interventions, followed by attitudes. Awareness of consequences had a large positive impact on personal norms and a smaller positive impact on attitudes. A negative relationship was found between information and attitudes. Personal norms and attitudes also acted as mediators between awareness of consequences, information and support. No differences were found between domestic and international tourists. The results are discussed and theoretical and practical implications outlined.